Warm Foot Bath Therapy and Jasmine Aromatherapy to Treat Insomnia in the Elderly - Anggia Astuti Astuti; Zainal Abidin; Rizeki Dwi Fibriansari; Devy Amanda (Health and Technology Journal (HTechJ), 2025)
Lack of sleep can harm the physical, mental, and emotional health, quality of life, cognitive function, and memory function of the elderly. Poor sleep quality can also directly affect health, with the risk of various problems such as hypertension, diabetes mellitus, stroke, obesity, heart disease, and several other conditions. Therefore, the need for effective non-pharmacological pain and symptom management strategies during sleep disorders is increasing. One recommended approach is relaxation therapy involving soaking the feet in warm water and jasmine aromatherapy before bedtime. This study aims to evaluate the effects of warm foot baths combined with jasmine aromatherapy on sleep quality and vital signs in older adults with insomnia. Using a case study design, the intervention was given to one participant, an 81-year-old woman diagnosed with moderate insomnia. The participant reported difficulty falling asleep, frequent waking during the night, dissatisfaction with her sleep quality, significant changes in sleep patterns, and insufficient rest. The therapy consisted of warm foot baths with jasmine aromatherapy, performed every night for five consecutive days before bedtime. To assess the effectiveness of the intervention, measurements were taken of changes in the Insomnia Severity Index (ISI) score, detailed observations of sleep patterns, and general monitoring of vital signs. The study showed a significant decrease in the ISI score from 19 (moderate insomnia) to 8 (mild insomnia). In addition, participants experienced improved sleep quality, characterized by sleeping through the night without waking up, increased sleep satisfaction, and adequate rest. Vital signs showed stabilization during the intervention period, indicating better physiological relaxation. These findings support using warm foot baths and jasmine aromatherapy as an effective nursing intervention to treat insomnia and improve sleep quality in the elderly.